THE RELATIONSHIP BETWEEN SLEEP QUALITY AND QUALITY OF LIFE IN THE ELDERLY IN ABELI SUBDISTRICT, KENDARI CITY: CROSS SECTIONAL STUDY: SLEEP QUALITY AND QUALITY OF LIFE - krismiadi, Dedi; Ningtias, Dwi Wulandari; Dina, Hasniah; Apriyanti, Apriyanti; Yusnayanti, Cici; Purnama, Prawara Aros (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Sleep is one of the basic human needs which is a physiological need and gives the body the opportunity to restore and provide energy and relieve tension. Aim: If the need for sleep is not of good quality, this condition will cause fatigue which will hinder the elderly in fulfilling their daily activities and can affect the quality of life of the elderly. Methods: This study is a quantitative study with a cross-sectional approach in the Abeli Subdistrict, Kendari City. A sample of 84 respondents was obtained through Consecutive Sampling. Results: The data was processed using the Fisher exact test, obtained ap value = 0.006 <0.05 which shows a relationship between sleep quality and the quality of life of the elderly in the Abeli sub-district of Kendari City.  Conclusion: Therefore, the elderly really need to pay attention to the quality of sleep in order to maintain a good quality of life so that the welfare of the elderly is created.